The effects of conformation and zwitterionic tautomerism on the structural and vibrational spectral data of anserine - Balcı, Kubilay; Akkaya, Yasemin; Collier, W. B.; Stricker, Moogega C.; Stover, D. D.; Ritzhaupt, G.; Koch, Andreas; Kleinpeter, Erich; AKYÜZ, SEVİM (Elsevier Science Bv, Po Box 211, 1000 AE Amsterdam, Netherlands, 2016)
In this study, the stable conformers of neutral anserine were searched by molecular dynamics simulations and energy minimization calculations using the MM2 force field. Thermochemical calculations at B3LYP/6-31G(d) level of theory followed these preliminary calculations. The results confirmed that neutral anserine has quite a flexible structure and many stable gauche and trans conformers at room temperature. Nevertheless, two are considerably more favourable in energy than the others and expected to dominate the gas-phase and matrix IR spectra of the molecule. The corresponding structural and vibrational spectral data for these two conformers of neutral anserine, whose relative stabilities were also examined by high-accuracy energy calculations carried out using G3MP2B3 method, and for the most stable conformer of anserine in zwitterion form were calculated at B3LYP/6-311++G(d,p) level of theory. The calculated harmonic force constants were refined using the Scaled Quantum Mechanical Force Field (SQM-FF) method and then used to produce the refined wavenumbers, potential energy distributions (PEDs) and IR and Raman intensities. These refined data together with the scaled harmonic wavenumbers obtained using another method, Dual Scale factors (DS), enabled us to correctly analyse the observed IR and Raman spectra of anserine and revealed the effects of conformation and zwitterionic tautomerism on its structural and vibrational spectral data. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Anserine; Matrix IR spectrum; Tautomerism; SQM-FF; Dual scale factors; Ab-Initio; Raman-Spectra; Force-Fields; Molecular Geometries; L-Histidine; Carnosine; Density; Ir; Complexes; Binding